USE OF CLUSTER ANALYSIS IN THE SELECTION OF VARIETIES AND HYBRIDS OF SPRING RAPE FOR CULTIVATION IN THE LEFT-BANK FOREST-STEPPE OF UKRAINE - Мельник, А. В. (Scientific Progress & Innovations, 2013)
Spring rape varieties and hybrids suitable for cultivation in the northern part of Left-Bank Forest-Steppe of Ukraine have been identified: PR45G72, PR45G73 hybrids, Siesta and Haydn, Olga, Aira, Baikal, Maria, Terra, Ataman varieties, which ensure the yield of more than 1.6 t/ha of seeds and oil yield of more than 0.6 t/ha. According to the results of cluster analysis several groups of varieties and hybrids (clusters) have been defined, namely: Aira and PR45G73 belong to the first group, the second group contains Mykitinetsky and Ataman, the third – Baikal and PR45G72, the fourth – Haydn and Terra – both are the selection of German firm “Norddeutsche Pflantsentsuht Hans-Georg Lembke KG”, the fifth cluster may contain Obriy and Oksamyt. While selecting the varieties of rape a producer is not recommended to use two or more accessions selections of one originator out of a single cluster, because in the same conditions they will respond similarly.